Growth opportunities and IPO initial performance. is there an interacting effect of public issue? / Siti Suhaila Abdul Rahman and Norliza Che-Yahya - Abdul Rahman, Siti Suhaila; Che-Yahya, Norliza (Universiti Teknologi MARA Shah Alam, 2020)
The declining rate on initial return of Malaysian IPOs over the past years have alarmed investors to astutely choose IPO firms for a better security of their investment's income. In an attempt to offer an aid for the danger on the loss of capital that the investors might suffer, this study is initiated to search for explanations on the variation of IPO returns particularly in the initial aftermarket. This study proposes "growth opportunities in an IPO firm" and "allocation of IPOs through public issue approach" as its main explanatory factors which the former acts as main explanatory variable while the latter serves as interacting variable. This study defines "growth opportunities of firms" as the possibility of an IPO firm to enlarge its market share over the long period. The "growth opportunities of firms" are measured by the total allocation amount received from the issuance of IPOs to activities (e.g., assets acquisition and business expansion) which possibly support growth of a firm in a future. To an extent, a higher amount of proceeds channeled to "growth activities" are expected to increase growth opportunities of firms such that will encourage higher participation on the shares of the issuing firms as well as higher returns of the shares. Nonetheless, "growth opportunities of firms" can be accurately gauged only if the amount of cash from the sale of IPOs are owned by the issuing firms. That is, the public issue approach that an IPO firm adopts when issue for its shares to public should finalize the final proceeds eligible to be allocated to any intended activities of the firm. Using a total 447 IPOs listed in Main Market and ACE Market of Bursa Malaysia from 2000 to 2018, tested using hierarchical regression models, this study found that the proceeds allocated to growth activities significantly positively influence initial return. However, this study is not able to produce a significant interaction effect of public issue on the main relationship tested earlier.